Menguji peran komitmen organisasi terhadap perawat wanita - Shofi Fadhila; Dewie Tri Wijayati (Jurnal Ilmu Manajemen, 2023)
This study aims to measure and analyze the effect of work-family conflict on employee performance through organizational commitment as a mediating variable for married female nurses at hospital X. This research is a causal study with a quantitative approach with a population of 129 married female nurses and sampling techniques using purposive sampling with a total of 98 samples. Data analysis in this study used SEM-PLS with the help of SmartPLS 4.0.9 software. The estimated coefficient is positive at 0.319, indicating that the higher the work-family conflict, the performance of female nurses at hospital X will also increase. The estimated coefficient is positive at 0.459, meaning that the higher the level of work-family conflict, the organizational commitment to female nurses at Hospital X will also increase. The estimated coefficient is positive by 0.358, indicating that as organizational commitment increases, employee performance of female nurses at hospital X will also increase, with a t-statistic value of 3.047 > 1.96, proving that organizational commitment contributes to mediating between work-family conflict on employee performance.